Compreensão e produção de fala em crianças com deficiência auditiva pré-lingual usuárias de implante coclear - Golfeto, Raquel Melo (2010)
Acquisitions of verbal functions in prelingually deaf children have shown progress in the listener s behavior, but less significant gains in the speaker s behavior. The aim of this study was to develop and assess the effectiveness of teaching procedures designed to develop listening comprehension and speech intelligibility in this population. Three studies were conducted. In the first one, subjects were taught conditional auditory-visual relations between dictated words and pictures, and between dictated words and printed words, along three successive learning problems. Two teenage girls with extensive sensory deprivation periods and late cochlear implants learned the auditory-visual relations and showed the emergence of equivalence relations, progressing from the learning relations with conventional words to learning relations between pseudo-words and abstract pictures. Study 2 investigated the effects of a curriculum of conditional discriminations between dictated words and pictures and between dictated and printed words to preschoolers and children acquiring literacy, thus extending the amount of experience with successive sets of words, in relation to Study 1. A multiple baseline design among word sets assessed the curriculum effects. Five of the seven participants learned the conditional discrimination and presented the emergence of equivalence relations, echoic behavior and naming pictures and printed words. Speech production scores, however, lag behind scores in matching tasks. In Study 3 participants learned conditional discriminations between dictated sentences and videoclip scenes. Different sentences were dictated, warranting overlapping of sentence elements, seeking to engender recombinative repertoires (in identifying new scenes formed by recombination of subject, verb and object of previous sentences). Participants demonstrated recombinative generalization and produced intelligible sentences. Results indicate the potential of the teaching procedures for the (re)habilitation of implant users. The persistence of the imbalance between speech production and auditory comprehension suggests important issues concerning the ontogenesis of the listener and speaker s repertoire.